A spherical Prussian blue positive electrode material for sodium ion battery and preparation method thereof
By introducing Fe doping into the positive electrode material of sodium ion battery, Fe doped Mn pyprus blue material with a porous hierarchical spherical structure was prepared, which solved the problem of poor rate performance and cycle stability of the existing materials, and achieved high rate performance and superior cycle performance.
Patent Information
- Application Number
- CN202211169321.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-23
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-09-23
AI Technical Summary
The existing sodium ion battery positive electrode materials, especially Fe pyprus blue materials, have poor permeability of the electrolyte and low rate performance, as well as Mn3+ ginger-Taylor effect, Mn2+ dissolution and structural phase change during charging and discharging, resulting in poor cycle stability.
By introducing Fe doping into the NaxMn[Fe(CN)6]y lattice, Fe doped Mn pyprusian blue material with a stable, highly dispersed porous hierarchical spherical structure was prepared. The chemical composition of this material is NaxMnyFe1-y[Fe(CN)6]z·nH2O. Solid-liquid two-phase synthesis is carried out by slightly soluble in mixed solvents with different volume ratios of anhydrous ethanol and water to form a new synthesis mechanism of Prussian blue.
High-rate performance and superior cycling performance are achieved, eased the ginger-Taylor effect of Mn3+, the dissolution and structural phase transition of Mn2+, and ensured the large gram capacity and high energy density of Prussian blue cathode material.
Smart Images

Figure CN115360346B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of positive electrode materials for sodium ion batteries, and more specifically relates to a spherical Prussian blue positive electrode material for sodium ion batteries and a preparation method thereof. Background Art
[0002] With the increasing energy crisis and carbon emission problems, the large-scale energy storage and utilization of discontinuous clean energy such as solar energy, wind energy, and geothermal energy is particularly important. Due to the abundant sodium resources on the earth, sodium-ion batteries are considered to have huge potential advantages in large-scale energy storage, and therefore have attracted widespread attention. The positive electrode material of sodium-ion batteries is one of the important factors that limit the performance of sodium-ion batteries. At present, the positive electrode materials of sodium-ion batteries are mainly divided into the following three categories: transition metal oxides, polyanions, and Prussian blue and its derivatives. Among them, the Prussian blue positive electrode material has an open large framework and tunnel structure, with a theoretical capacity of up to 170mAh / g, low raw material cost, simple and environmentally friendly synthesis, and is considered to be one of the most promising positive electrode materials for sodium-ion batteries. Iron-based Prussian blue material Na x Fe[Fe(CN)6] y The platform voltage of Prussian blue is relatively low (~3.0V) and the capacity is relatively low, which cannot meet the needs of current large-scale energy storage applications. x Mn[Fe(CN)6] y The working voltage is as high as 3.5V, with higher specific capacity and energy density. Tang et al. 2+ Chelation to reduce Mn 2+ The coprecipitation reaction rate with ferrocyanide ion is to obtain a uniform and stable solid cubic Na x Mn[Fe(CN)6] y Positive electrode materials (Adv Funct Mater 2020, 30(10), 1908754), but due to the large particle size (about 5 μm), the electrolyte permeability is poor and its rate performance is low. x Mn[Fe(CN)6] y During the charge and discharge process, there is Mn 3+ The Chiang-Taylor effect, Mn 2+ Problems such as dissolution and structural phase change lead to poor cycle stability.
[0003] In order to solve the above-mentioned problem of Prussian blue electrode, Na x Mn[Fe(CN)6] y Introducing metal atoms such as Fe, Ni and Co into the lattice is considered to be the most effective method. Huang et al. x Mn[Fe(CN)6]y Inactive Ni doping was performed to improve the cycle stability of the Prussian blue electrode (Small 2018, 14 (28), 1801246). However, the inactive Ni element doping instead of the active Mn element leads to a decrease in the specific capacity of the Prussian blue, while the active Co element substitution will result in high production costs. Therefore, the low-cost active Fe element doping is better than the doping of Ni and Co elements, and is more suitable for industrial promotion. Gong et al. used dry ball milling solid phase to synthesize nano Mn-based Prussian blue (about 50nm) with different Fe doping amounts, but the solid phase ball milling method not only consumes a lot of energy, but also the particles will be seriously agglomerated, resulting in very poor battery performance (J Nanopart Res 2019, 21, 274). Therefore, in the current existing technology, the Fe-doped Mn-based Prussian blue material obtained has the problem of excessively large micron particle size or serious agglomeration of nanoparticles, resulting in poor rate performance and cycle stability. Summary of the invention
[0004] In view of this, one of the objects of the present invention is to provide a spherical Prussian blue positive electrode material for a sodium ion battery, wherein the chemical composition of the positive electrode material is Na x Mn y Fe 1-y [Fe(CN)6] z nH2O is a Fe-doped Mn-based Prussian blue material, which has a stable, highly dispersed porous hierarchical spherical structure, ensuring high rate performance and good cycle stability. The second object of the present invention is to provide a method for preparing a spherical Prussian blue positive electrode material for a sodium ion battery, which has low raw material cost, simple preparation process, easy control, low energy consumption, and is suitable for industrial promotion.
[0005] In order to achieve the above object, the technical solution of the present invention is as follows:
[0006] A method for preparing a spherical Prussian blue positive electrode material for a sodium ion battery comprises the following steps:
[0007] (1) dispersing the raw material sodium ferrocyanide in anhydrous ethanol to obtain a milky white uniform dispersion, and dissolving a divalent manganese salt and a divalent iron salt in deionized water and stirring to dissolve to obtain a uniform mixed metal salt solution;
[0008] (2) slowly dripping the mixed metal salt solution in step (1) into the above dispersion, reacting under certain conditions, and then centrifuging or filtering to obtain a blue precipitate;
[0009] (3) The blue precipitate in step (2) is washed and dried to obtain a spherical Prussian blue positive electrode material.
[0010] Furthermore, the divalent manganese salt includes one or more of MnSO4·H2O, Mn(NO3)2·H2O or MnCl2, and the divalent iron salt includes one or more of FeSO4·7H2O, Fe(NO3)2 or FeCl2·4H2O.
[0011] Furthermore, the molar ratio of the divalent manganese salt to the divalent iron salt is 1:(0.01-100), the molar ratio of the sodium ferrocyanide to the metal salt (total) is 1:(1-2), the volume ratio of the sodium ferrocyanide dispersion to the mixed metal salt solution is 1:(0.1-1), and the concentration of the sodium ferrocyanide dispersion is 5-50 g / L.
[0012] Furthermore, the dropping speed of the mixed metal salt solution is 1-100 mL / min, the reaction temperature is 5-50° C., the stirring speed is 100-1500 rpm, and the reaction time is 12-24 h.
[0013] Furthermore, the washing solvent includes deionized water or anhydrous ethanol, and the drying condition is drying at 60-100° C. for more than 2 hours.
[0014] The chemical composition of the spherical Prussian blue positive electrode material for sodium ion batteries obtained by the present invention is Na x Mn y Fe 1-y [Fe(CN)6] z ·nH2O, wherein the value of x is 0.01 to 2, the value of y is 0.01 to 0.99, the value of z is 0.01 to 1, and the value of n is 0.01 to 3, and the positive electrode material is a porous hierarchical spherical structure.
[0015] The present invention also relates to a sodium ion battery whose positive electrode material is the aforementioned spherical Prussian blue.
[0016] It can be seen from the above technical solutions that, compared with the prior art, the present invention provides a spherical Prussian blue positive electrode material for sodium ion batteries and a preparation method thereof, which has the following excellent effects:
[0017] (1) The present invention provides a spherical Prussian blue positive electrode material for a sodium ion battery, wherein the positive electrode material is an Fe-doped Mn-based Prussian blue material having a chemical formula of Na x Mn y Fe 1-y [Fe(CN)6] z nH2O, the doping of cheap Fe elements not only provides sodium storage active sites, but also relieves the 3+ The Chiang-Taylor effect, Mn 2+The dissolution and structural phase change of Prussian blue cathode materials ensure the large gram capacity, high rate performance and excellent cycle performance;
[0018] (2) The preparation method of the spherical Prussian blue positive electrode material for sodium ion batteries of the present invention utilizes the characteristics of sodium ferrocyanide being slightly soluble in anhydrous ethanol and easily soluble in water, resulting in differences in the solubility of sodium ferrocyanide in mixed solvents of anhydrous ethanol and water in different volume ratios, so that the reaction system presents a solid-liquid two-phase, forming a new synthesis mechanism of Prussian blue. The reaction mechanism of the spherical Prussian blue positive electrode material for sodium ion batteries of the present invention is: First, a small amount of solid phase sodium ferrocyanide partially dissolves in anhydrous ethanol to produce Na + and [Fe(CN)6] 4- ions, then Na + and [Fe(CN)6] 4- With water-soluble Mn 2+ and Fe 2+ A coprecipitation reaction occurs in the liquid phase. The new synthesis mechanism of Prussian blue in the two-phase synthesis preparation process helps to reduce the reaction rate and affect the crystal growth process. The prepared Prussian blue is a stable, highly dispersed porous hierarchical spherical micro-nano structure self-assembled by nanocubes, with small grain size, large specific surface area and high sodium ion migration rate, ensuring that high platform voltage, high rate performance and good cycle stability can be obtained;
[0019] (3) The raw materials used in the present invention are cheap and easily available, the synthesis process is safe, controllable and energy-efficient, and has large-scale production capabilities. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to further illustrate the technical solutions and implementation cases in the present invention, the following is a brief description of the test drawings used in the existing examples or technical processes. It is worth noting that the drawings listed below are only some implementation cases in the present invention. For technicians in the same field, other drawings can be obtained based on the provided drawings without creative work.
[0021] Figure 1 This is the X-ray diffraction pattern of the Prussian blue prepared in Example 1;
[0022] Figure 2 This is a scanning electron microscope image of the Prussian blue prepared in Example 1;
[0023] Figure 3 This is the X-ray diffraction pattern of Prussian blue prepared in Example 2;
[0024] Figure 4 This is a scanning electron microscope image of the Prussian blue prepared in Example 2;
[0025] Figure 5 This is the X-ray diffraction pattern of the Prussian blue prepared in Example 3;
[0026] Figure 6 This is a scanning electron microscope image of the Prussian blue prepared in Example 3;
[0027] Figure 7 This is the X-ray diffraction pattern of Prussian blue prepared in Comparative Example 1;
[0028] Figure 8 This is a scanning electron microscope image of the Prussian blue prepared in Comparative Example 1;
[0029] Fig. 9 This is the X-ray diffraction pattern of Prussian blue prepared in Comparative Example 2;
[0030] Fig.10 This is a scanning electron microscope image of the Prussian blue prepared in Comparative Example 2; DETAILED DESCRIPTION
[0031] The following will further describe the process and technology of the embodiment of the present invention in detail in conjunction with the accompanying drawings of the test results of the embodiment of the present invention. In addition, the embodiments described in this patent are only some examples of the present invention, not all. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0032] The embodiment of the present invention discloses a method for preparing a spherical Prussian blue positive electrode material for a sodium ion battery, and the specific steps include:
[0033] (1) adding a raw material of sodium ferrocyanide (Na4Fe(CN)6·10H2O) to anhydrous ethanol and stirring for 15 minutes to obtain a 5-50 g / L milky white sodium ferrocyanide dispersion; weighing a divalent manganese salt and a divalent iron salt according to a ratio of the amount of manganese salt to the divalent iron salt of 1:(0.01-100) and a ratio of the amount of sodium ferrocyanide to the metal salt (total) of 1:(1-2), adding the divalent manganese salt and the divalent iron salt to a certain volume of deionized water, ensuring that the volume ratio of the sodium ferrocyanide dispersion to the mixed metal salt solution is 1:(0.1-1), stirring until fully dissolved to obtain a transparent mixed metal salt solution;
[0034] (2) slowly dripping the mixed metal salt solution in step (1) into the sodium ferrocyanide dispersion through a constant pressure funnel or a peristaltic pump at a dripping rate of 1 to 100 mL / min, and reacting at a reaction temperature of 5 to 50° C. and a stirring rate of 100 to 1500 rpm for 12 to 24 hours, followed by filtering or centrifuging to obtain a blue Prussian blue precipitate;
[0035] (3) The Prussian blue precipitate in step (2) is then filtered and washed with a detergent, and then placed in an oven at 60-100° C. for drying for a drying time of more than 2 hours to obtain the spherical Prussian blue positive electrode material for sodium ion batteries of the present invention.
[0036] Furthermore, the divalent manganese salt in step (1) includes one or more of MnSO4·H2O, Mn(NO3)2·H2O or MnCl2, and the divalent iron salt includes one or more of FeSO4·7H2O, Fe(NO3)2 or FeCl2·4H2O.
[0037] Furthermore, the detergent in step (3) includes deionized water or anhydrous ethanol.
[0038] The technical solution of the present invention will be further described below in conjunction with specific embodiments:
[0039] Example 1
[0040] (1) Weigh 1.21 g of sodium ferrocyanide (Na4Fe(CN)6·10H2O) and add it to 50 mL of anhydrous ethanol. Stir for 15 minutes to obtain a 24 g / L milky white sodium ferrocyanide dispersion. Weigh 0.51 g of manganese sulfate (MnSO4·H2O) and 0.56 g of ferrous sulfate (FeSO4·7H2O) and dissolve them in 50 mL of deionized water. Stir and dissolve to obtain a transparent mixed metal salt solution with a metal ion (total) concentration of 0.1 mol / L.
[0041] (2) slowly dripping the mixed metal salt solution in step (1) into the sodium ferrocyanide dispersion through a constant pressure funnel at a dripping rate of 1 mL / min, while stirring at 1000 rpm at 25° C. for 16 h, and then filtering to obtain a blue Prussian blue precipitate;
[0042] (3) The Prussian blue precipitate in step (2) is then washed alternately with water / ethanol, wherein the water is washed twice and the ethanol is washed once, until the impurities are completely removed. The precipitate is then placed under vacuum drying at 60° C. for 24 h to obtain the spherical Prussian blue positive electrode material Na prepared in the present invention for sodium ion batteries. 0.89 Mn 0.51 Fe 0.49 [Fe(CN)6] 0.60 1.48H2O.
[0043] Example 2
[0044] (1) Weigh 1.21 g of sodium ferrocyanide (Na4Fe(CN)6·10H2O) and add it to 80 mL of anhydrous ethanol, and stir for 15 minutes to obtain a 15 g / L milky white sodium ferrocyanide dispersion; weigh 0.38 g of manganese chloride (MnCl2) and 0.39 g of ferrous chloride (FeCl2·4H2O) and dissolve them in 20 mL of deionized water, stir and dissolve to obtain a transparent mixed metal salt solution, and the metal ion (total) concentration is 0.25 mmol / L;
[0045] (2) slowly dripping the mixed metal salt solution in step (1) into the sodium ferrocyanide dispersion through a constant pressure funnel at a dripping rate of 2 mL / min, while stirring at 500 rpm for 20 h at 25° C., and then filtering to obtain a Prussian blue precipitate;
[0046] (3) The Prussian blue precipitate in step (2) is then washed alternately with water / ethanol, wherein the water is washed twice and the ethanol is washed once, until the impurities are completely removed. The precipitate is then placed under vacuum drying at 80° C. for 24 h to obtain the spherical Prussian blue positive electrode material Na prepared in the present invention for sodium ion batteries. 1.25 Mn 0.80 Fe 0.575 [Fe(CN)6]·0.90H2O.
[0047] Example 3
[0048] (1) Weigh 1.21 g of sodium ferrocyanide (Na4Fe(CN)6·10H2O) and add it to 80 mL of anhydrous ethanol. Stir for 15 minutes to obtain a 15 g / L milky white sodium ferrocyanide dispersion. Weigh 0.59 g of manganese nitrate (Mn(NO3)2·H2O) and 0.36 g of ferrous nitrate (Fe(NO3)2) and dissolve them in 20 mL of deionized water. Stir and dissolve to obtain a transparent mixed metal salt solution with a metal ion (total) concentration of 0.25 mol / L.
[0049] (2) slowly dripping the mixed metal salt solution in step (1) into the sodium ferrocyanide dispersion through a constant pressure funnel at a dripping rate of 100 mL / min, while stirring at 800 rpm at 50° C. for 24 h, and then centrifuging to obtain a Prussian blue precipitate;
[0050] (3) The Prussian blue precipitate in step (2) is then washed alternately with water / ethanol, wherein the water is washed twice and the ethanol is washed once, until the impurities are completely removed. The precipitate is then placed under vacuum drying at 70° C. for 22 h to obtain the spherical Prussian blue positive electrode material Na prepared in the present invention for sodium ion batteries. 1.03 Mn 0.62 Fe 0.38 [Fe(CN)6] 0.64 1.75H2O.
[0051] Comparative Example 1
[0052] (1) Weigh 1.21 g of sodium ferrocyanide (Na4Fe(CN)6·10H2O) and add it to 80 mL of deionized water, stir well to obtain a 15 g / L yellow sodium ferrocyanide solution; weigh 0.51 g of manganese sulfate (MnSO4·H2O) and 0.56 g of ferrous sulfate (FeSO4·7H2O) and add them to 20 mL of deionized water, stir to obtain a transparent mixed metal salt solution with a metal ion (total) concentration of 0.25 mol / L;
[0053] (2) adding the mixed metal salt solution in step (1) dropwise into the sodium ferrocyanide solution at a rate of 1 mL / min, stirring at 500 rpm for 16 h at 25° C., and then centrifuging to obtain a Prussian blue precipitate;
[0054] (3) The Prussian blue precipitate in step (2) is then washed alternately with water / ethanol, wherein the water is washed twice and the ethanol is washed once, until the impurities are completely removed. It is then placed in a vacuum dryer at 60° C. for 24 hours, and finally a cubic Prussian blue positive electrode material Na for sodium ion batteries is obtained. 1.13 Mn 0.73 Fe 0.42 [Fe(CN)6]·1.24H2O.
[0055] Comparative Example 2
[0056] (1) Weigh 1.21 g of sodium ferrocyanide (Na4Fe(CN)6·10H2O) and add it to 100 mL of anhydrous ethanol. Stir for 15 minutes to obtain a 12 g / L milky white sodium ferrocyanide dispersion. Weigh 0.51 g of manganese sulfate (MnSO4·H2O) and 0.56 g of ferrous sulfate (FeSO4·7H2O) and add them directly to the dispersion.
[0057] (2) stirring the mixed solution in step (1) at 25° C. and 500 rpm for 16 h, and then filtering to obtain a Prussian blue precipitate;
[0058] (3) The Prussian blue precipitate in step (2) is then washed alternately with water / ethanol, wherein the water is washed twice and the ethanol is washed once, until the impurities are completely removed. It is then placed in a vacuum dryer at 60° C. for 24 hours to finally obtain a spherical Prussian blue positive electrode material Na for sodium ion batteries. 0.96 Mn 0.67 Fe 0.33 [Fe(CN)6] 0.74 ·2.08H2O.
[0059] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0060] The spherical Prussian blue cathode material for sodium ion batteries prepared in each example was characterized and tested, and the test conditions were as follows:
[0061] (1) X-ray diffraction (XRD) test:
[0062] The test was conducted by using a Rigaku-D / max-2550p X-ray powder diffractometer of Hitachi, Japan, using Cu-Kα as the radiation source, with a wavelength of 1.5046λ; using a Ni filter, a tube current of 40mA, a tube voltage of 40KV, a scanning range of 10° to 90°, a scanning speed of 20° / min, and a step length of 0.02°. The material was placed in a glass slide and flattened, and the glass slide was embedded in the center of the instrument experimental slot for testing; the identification of the physical phase and the crystal structure information were analyzed by JADE 6.0 software.
[0063] (2) Scanning electron microscopy characterization:
[0064] The morphology of the sodium ion battery electrode materials prepared in each implementation case was observed using a S-4800 scanning electron microscope tester produced by HITACHI with an acceleration voltage of 15KV. The specific test results are as follows:
[0065] Figure 1 This is the X-ray diffraction diagram of the spherical Prussian blue positive electrode material for sodium ion battery prepared in Example 1, where the X-axis is the angle 2θ of the X-ray scanning and the ordinate is the intensity of the X-ray. Figure 1 It can be seen that the Prussian blue positive electrode material has a characteristic peak on the (200) crystal plane at a scanning angle of 16.92°, a characteristic peak on the (220) crystal plane at a scanning angle of 24.12°, a characteristic peak on the (400) crystal plane at a scanning angle of 34.18°, a characteristic peak on the (420) crystal plane at a scanning angle of 38.56°, a characteristic peak on the (422) crystal plane at a scanning angle of 42.46°, a characteristic peak on the (440) crystal plane at a scanning angle of 49.39°, a characteristic peak on the (600) crystal plane at a scanning angle of 52.78°, and a characteristic peak on the (620) crystal plane at a scanning angle of 55.77°. It belongs to the Fm-3m space group and has no impurity peaks in the X-ray diffraction pattern, indicating that the positive electrode material is a pure phase substance.
[0066] Figure 2This is a scanning electron microscope image of the spherical Prussian blue positive electrode material for a sodium ion battery obtained in Example 1. It can be observed that the Prussian blue positive electrode material is a spherical structure composed of nanometer-scale cubic grains. The size of the nanocube is ~100nm, and the size of the spherical structure is 3~5μm.
[0067] Figure 3 This is the X-ray diffraction diagram of the spherical Prussian blue positive electrode material for sodium ion batteries prepared in Example 2, where the X-axis is the angle 2θ of the X-ray scanning and the ordinate is the intensity of the X-ray. Figure 1 It can be seen that the Prussian blue positive electrode material has a characteristic peak on the (200) crystal plane at a scanning angle of 16.88°, a characteristic peak on the (220) crystal plane at a scanning angle of 24.06°, a characteristic peak on the (400) crystal plane at a scanning angle of 34.1°, a characteristic peak on the (420) crystal plane at a scanning angle of 38.42°, a characteristic peak on the (422) crystal plane at a scanning angle of 42.38°, a characteristic peak on the (440) crystal plane at a scanning angle of 49.4°, a characteristic peak on the (600) crystal plane at a scanning angle of 52.62°, and a characteristic peak on the (620) crystal plane at a scanning angle of 55.67°. It belongs to the Fm-3m space group and has no impurity peaks in the X-ray diffraction pattern, indicating that the positive electrode material is a pure phase substance.
[0068] Figure 4 This is a scanning electron microscope image of the spherical Prussian blue positive electrode material for sodium ion batteries obtained in Example 2. It can be observed that the Prussian blue material is a porous hierarchical spherical structure composed of nanocubes. The size of the nanocube is ~100nm, the size of the hierarchical spherical is ~2μm, and the dispersion is good.
[0069] Figure 5 This is the X-ray diffraction diagram of the spherical Prussian blue positive electrode material for sodium ion battery prepared in Example 3, where the X-axis is the angle 2θ of the X-ray scanning and the ordinate is the intensity of the X-ray. Figure 1 It can be seen that the Prussian blue positive electrode material has a characteristic peak on the (200) crystal plane at a scanning angle of 17.48°, a characteristic peak on the (220) crystal plane at a scanning angle of 24.84°, a characteristic peak on the (400) crystal plane at a scanning angle of 34.44°, a characteristic peak on the (420) crystal plane at a scanning angle of 38.53°, a characteristic peak on the (422) crystal plane at a scanning angle of 42.03°, a characteristic peak on the (440) crystal plane at a scanning angle of 49.61°, a characteristic peak on the (600) crystal plane at a scanning angle of 50.94°, and a characteristic peak on the (620) crystal plane at a scanning angle of 55.67°. It belongs to the Fm-3m space group and has no impurity peaks in the X-ray diffraction pattern, indicating that the positive electrode material is a pure phase substance.
[0070] Figure 6 This is a scanning electron microscope image of the spherical Prussian blue positive electrode material for a sodium ion battery obtained in Example 3. It can be observed that the Prussian blue material is a spherical structure composed of nanocubic particles, but some are broken. The size of the nanocubic particles is 50 to 200 nm, and the size of the spherical structure is ~2 μm.
[0071] Figure 7 This is the X-ray diffraction diagram of the cubic Prussian blue positive electrode material for sodium ion batteries prepared in Comparative Example 1, where the X-axis is the angle 2θ of the X-ray scanning and the ordinate is the intensity of the X-ray. Figure 1 It can be seen that the Prussian blue positive electrode material has a characteristic peak on the (200) crystal plane at a scanning angle of 16.94°, a characteristic peak on the (220) crystal plane at a scanning angle of 24.08°, a characteristic peak on the (400) crystal plane at a scanning angle of 34.34°, a characteristic peak on the (420) crystal plane at a scanning angle of 38.56°, a characteristic peak on the (422) crystal plane at a scanning angle of 42.38°, a characteristic peak on the (440) crystal plane at a scanning angle of 49.4°, a characteristic peak on the (600) crystal plane at a scanning angle of 52.36°, and a characteristic peak on the (620) crystal plane at a scanning angle of 55.67°. It belongs to the Fm-3m space group and has no impurity peaks in the X-ray diffraction pattern, indicating that the positive electrode material is a pure phase substance.
[0072] Figure 8 This is a scanning electron microscope image of the cubic Prussian blue positive electrode material for sodium ion batteries obtained in Comparative Example 1. It can be observed that the morphology of the Prussian blue material is a cubic morphology composed of agglomerated nanoparticles, wherein the nanoparticle size is ∼100 nm and the cubic structure is 2 to 8 μm.
[0073] Fig. 9 This is the X-ray diffraction diagram of the spherical Prussian blue positive electrode material for sodium ion battery prepared in Comparative Example 2, where the X-axis is the angle 2θ of the X-ray scanning and the ordinate is the intensity of the X-ray. Figure 1It can be seen that the Prussian blue positive electrode material has a characteristic peak on the (200) crystal plane at a scanning angle of 16.82°, a characteristic peak on the (220) crystal plane at a scanning angle of 23.96°, a characteristic peak on the (400) crystal plane at a scanning angle of 34.1°, a characteristic peak on the (420) crystal plane at a scanning angle of 38.35°, a characteristic peak on the (422) crystal plane at a scanning angle of 42.19°, a characteristic peak on the (440) crystal plane at a scanning angle of 49.17°, a characteristic peak on the (600) crystal plane at a scanning angle of 52.26°, and a characteristic peak on the (620) crystal plane at a scanning angle of 55.42°. It belongs to the Fm-3m space group and has no impurity peaks in the X-ray diffraction pattern, indicating that the positive electrode material is a pure phase substance.
[0074] Fig.10 This is a scanning electron microscope image of the spherical Prussian blue positive electrode material for a sodium ion battery obtained in Comparative Example 2. It can be observed that the Prussian blue material is a spherical structure composed of nanocubic particles. The size of the nanocubic particles is 400-800nm, and the size of the spherical structure is 3-5μm.
[0075] Different Prussian blue positive electrode materials for sodium ion batteries prepared in various examples were used as positive electrode active materials for sodium ion batteries. The positive electrode active materials were mixed with a binder (polyvinylidene fluoride PVDF) and a conductive agent (Super P) at a mass ratio of 8:1:1, and dimethylpyrrolidone (NMP) was added as a solvent to mix and stir into a uniform slurry. The slurry was evenly applied on an aluminum foil, cut into thin sheets after drying as the positive electrode, metallic sodium was used as the negative electrode, a glass fiber membrane was used as a separator, and 1.0 mol / L NaClO4 / EC (ethylene carbonate) + PC (polycarbonate) + FEC (fluoroacetate) (EC: PC: FEC = 0.45: 0.45: 0.05, vol) was used as the electrolyte, and a CR2032 button battery was assembled in an argon glove box.
[0076] The above-assembled button batteries were tested using the Land battery tester produced by Wuhan Jinnuo Electronics Co., Ltd. The test conditions and results are as follows:
[0077] The button battery was subjected to constant current charge and discharge test, and the charge and discharge voltage range was 2 to 4.2 V. Among Examples 1 to 3, the electrochemical performance of the Prussian blue electrode of Example 2 was the best. The initial specific capacity of the battery was 119 mAh / g at a current density of 100 mA / g, and the discharge specific capacity retention rate after 200 cycles was 86.5%, while the capacity of Comparative Example 1 and Comparative Example 2 after 200 cycles was only 42% and 30%. In addition, the discharge specific capacity retention rate of the Prussian blue electrode in Example 2 after 500 cycles was still 68%, and the coulomb efficiency of each cycle was close to 99%; the specific data are shown in Table 1
[0078] Table 1 Test results
[0079]
[0080] The content of the present invention is not limited to the content of the above embodiments. The combination of one or more embodiments can also achieve the purpose of the present invention.
[0081] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the method disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part description.
[0082] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a spherical Prussian blue positive electrode material for a sodium ion battery, characterized in that: The chemical composition of the positive electrode material is Na x Mn y Fe 1-y [Fe(CN)6] z ∙nH2O, wherein the value of x is 0.01-2, the value of y is 0.01-0.99, the value of z is 0.01-1, and the value of n is 0.01-3, and the positive electrode material is a porous hierarchical micro-nano spherical structure; The specific steps include: (1) dispersing the raw material sodium ferrocyanide in anhydrous ethanol to obtain a milky white uniform dispersion, and dissolving a divalent manganese salt and a divalent iron salt in deionized water and stirring to dissolve to obtain a uniform mixed metal salt solution; (2) slowly dripping the mixed metal salt solution in step (1) into the above dispersion, reacting under certain conditions, and then centrifuging or filtering to obtain a blue precipitate; (3) The blue precipitate in step (2) is washed and dried to obtain a spherical Prussian blue positive electrode material.
2. The method for preparing the spherical Prussian blue positive electrode material for sodium ion battery according to claim 1, characterized in that: In the step (1), the divalent manganese salt includes one or more of MnSO4∙H2O, Mn(NO3)2·H2O or MnCl2, and the divalent iron salt includes one or more of FeSO4∙7H2O, Fe(NO3)2 or FeCl2∙4H2O.
3. The method for preparing the spherical Prussian blue positive electrode material for sodium ion battery according to claim 1, characterized in that: In the step (1), the ratio of the amount of divalent manganese salt to the amount of divalent iron salt is 1:(0.01-100), the ratio of the amount of sodium ferrocyanide to the mixed metal salt is 1:(1-2), the volume ratio of the sodium ferrocyanide dispersion to the mixed metal salt solution is 1:(0.1-1), and the concentration of the sodium ferrocyanide dispersion is 5-50 g / L.
4. The method for preparing a spherical Prussian blue positive electrode material for a sodium ion battery according to claim 1, characterized in that : The dropping speed of the mixed metal salt solution in step (2) is 1~100mL / min.
5. The method for preparing a spherical Prussian blue positive electrode material for a sodium ion battery according to claim 1, characterized in that : In the step (2), the reaction temperature is 5-50°C, the stirring speed is 100-1500 rpm, and the reaction is carried out for 12-24 h.
6. The method for preparing a spherical Prussian blue positive electrode material for a sodium ion battery according to claim 1, characterized in that : In step (3), the detergent includes deionized water or anhydrous ethanol, the drying temperature is 60~100°C, and the drying time is >2h.
Citation Information
Patent Citations
Prussian blue positive electrode material, continuous preparation method thereof and sodium ion battery
CN115072741A